Efficiency improvement by incorporating 1-methyl-3-propylimidazolium iodide ionic liquid in gel polymer electrolytes for dye-sensitized solar cells. (1st September 2015) - Ng, H.M.; Ramesh, S.; Ramesh, K.
Abstract: Dye-sensitized solar cells (DSSCs) based on gel polymer electrolytes is a promising photovoltaic application which has been developed to solve the problem of liquid electrolyte leakage and improving the stability of the DSSCs. With the aim of replacing these liquid electrolytes for the applications of DSSCs, in this research we have prepared and optimized gel polymer electrolytes (GPE) consisting of poly[1-vinylpyrrolidone-co-vinyl acetate] (P[VP-co-VAc]), potassium iodide (KI), iodine (I2 ), ethylene carbonate (EC), propylene carbonate (PC) and 1-methyl-3-propylimidazolium iodide (MPIm + I − ) ionic liquid. The highest ionic conductivity obtained for this system is 3.13 × 10 −3  S cm −1 at room temperature. Fourier transform infrared (FTIR) studies confirmed the complexation of the P(VP-co-VAc)-based gel polymer electrolytes. These GPEs were then assembled into DSSCs with the configuration of glass/FTO/TiO2 /N3 dye/electrolyte/Pt/FTO/glass. The resultant DSSCs from P(VP-co-VAc)-based conducting gel electrolytes display power conversion efficiencies of 4.67% with maximum short circuit current density (jsc ) of 11.98 mA cm −2, open circuit voltage (Voc ) of 0.59 V and fill factor of 66% at 15 wt.% of 1-methyl-3-propylimidazolium iodide under standard light intensity of 100 mW cm −2 irradiation of AM 1.5 sunlight. Electrochemical impedance studies of the DSSCs were conducted and results indicate that the addition of MPIm + I − increases the recombination process of the excited electron with I3 − in the electrolyte which leads to shortening of the electron lifetime of the DSSCs. The electrocatalytic activity of the DSSC has also been investigated using Tafel polarization studies.